Caring behaviors by nurses in patients’ perceptions and experiencing an anxiety during hospitalization - Herwan Herwan; Teguh Pribadi (Malahayati International Journal of Nursing and Health Science, 2019)
Background: Feeling anxious due to lack of attention from the surroundings can be solved by providing a good caring performance from the health workers. The nursing experts place caring as the core principle of a nurse in performing his work. Caring behavior refers to giving attention to patients, respecting others, and showing empathy so that a nurse should maintain the relationship with the patients by having this the patients can commit and be responsible with them.Purpose: Knowing nursing caring behavior on anxiety level of hospitalized patients.Methods: This study was a quantitative study. The design was analytical with cross sectional approach. The population of the study consisted of 262 adult patients in average registered at Ryacudu General Hospital, Kotabumi Lampung. The elder and pediatric inpatients were excluded. The samples were 79 respondents. The sampling technique was accidental sampling.Results: Based on the statistical analysis, the p value was 0.487 or the p value > 0.05, there wasn’t nursing caring behavior on anxiety level of hospitalized patients.Conclusion: The health practitioners should improve their nursing quality by following nurse training about therapeutic communication. It is expected that health workers can increase caring so that patient anxiety can be reduced and can improve the quality of health services by providing training to all nursing staff on good and correct therapeutic communication.